Empirical Analysis of Global-Scale Natural Data and Analogue Seismotectonic Modelling Data to Unravel the Seismic Behaviour of the Subduction Megathrust - Funiciello, Francesca; Corbi, Fabio; Heuret, Arnauld; Piromallo, Claudia; Rosenau, Matthias (Frontiers in Earth Science, 2020)
Subduction megathrusts host the Earth's greatest earthquakes as the 1960 Valdivia (Mw 9.5, Chile), the largest earthquake instrumentally recorded, and the recent 2004 Sumatra-Andaman (Mw 9.2, Indonesia), 2010 Maule (Mw 8.8, Chile), and 2011 Tohoku-Oki (Mw 9.1, Japan) earthquakes triggering devastating tsunamis and representing a major hazard to society. Unravelling the spatio-temporal pattern of these events is thus a key for seismic hazard assessment of subduction zones. This paper reviews the current state of knowledge of two research areas - analysis of global-scale natural data and analogue seismotectonic modelling - devoted to study cause-effect relationships between subduction zone parameters and the megathrust seismogenic behavior. The combination of the two approaches allows drawing appropriately from multiple disciplines with the aim of highlighting the geodynamic conditions that may favor the occurrence of giant megathrust earthquakes.